Implant decontamination with phosphoric acid during surgical peri-implantitis treatment: a RCT - Diederik F. M. Hentenaar; Yvonne C. M. De Waal; Hans Strooker; Henny J. A. Meijer; Arie-Jan Van Winkelhoff; Gerry M. Raghoebar (SpringerOpen, 2017)
Abstract Background Peri-implantitis is known as an infectious disease that affects the peri-implant soft and hard tissue. Today, scientific literature provides very little evidence for an effective intervention protocol for treatment of peri-implantitis. The aim of the present randomized controlled trial is to evaluate the microbiological and clinical effectiveness of phosphoric acid as a decontaminating agent of the implant surface during surgical peri-implantitis treatment. Methods Peri-implantitis lesions were treated with resective surgical treatment aimed at peri-implant granulation tissue removal, bone recontouring, and pocket elimination. Fifty-three implant surfaces in 28 patients were mechanically cleaned and treated with either 35% phosphoric etching gel (test group) or sterile saline (control group). Microbiological samples were obtained during surgery; clinical parameters were recorded at baseline and at 3 months after treatment. Data were analyzed using multi-variable linear regression analysis and multilevel statistics. Results Significant immediate reductions in total anaerobic bacterial counts on the implant surface were found in both groups. Immediate reduction was greater when phosphoric acid was used. The difference in log-transformed mean anaerobic counts between both procedures was not statistical significant (p = 0.108), but there were significantly less culture-positive implants after the decontamination procedure in the phosphoric acid group (p = 0.042). At 3 months post-surgery, 75% of the implants in the control group and 63.3% of the implants in the test group showed disease resolution. However, no significant differences in clinical and microbiological outcomes between both groups were found. Conclusions The application of 35% phosphoric acid after mechanical debridement is superior to mechanical debridement combined with sterile saline rinsing for decontamination of the implant surface during surgical peri-implantitis treatment. However, phosphoric acid as implant surface decontaminant does not seem to enhance clinical outcomes on a 3-month follow-up. Trial registration Netherlands National Trial Register, NTR5185 (www.trialregister.nl)